Role of increased cytosolic free calcium in the pathogenesis of rabbit proximal tubule cell injury and protection by glycine or acidosis. - Weinberg, J M (1991)
To assess the role of increased cytosolic free calcium (Caf) in the pathogenesis of acute proximal tubule cell injury and the protection afforded by exposure to reduced medium pH or treatment with glycine, fura-2-loaded tubules were studied in suspension and singly in a superfusion system. The Ca2+ ionophore, ionomycin, increased Caf to micromolar levels and rapidly produced lethal cell injury as indicated by loss of lactate dehydrogenase to the medium by suspended tubules and accelerated leak of fura and failure to exclude Trypan blue by superfused tubules. Decreasing medium Ca2+ to 100 nM prevented the ionomycin-induced increases of Caf and the injury. Reducing medium pH from 7.4 to 6.9 or adding 2 mM glycine to the medium also prevented the cell death, but did not prevent the increase of Caf to micromolar levels. Cells treated with 1799, an uncoupler of oxidative phosphorylation which produced severe adenosine triphosphate (ATP) depletion, did not develop increases of Caf until just before loss of viability. Preventing these increases of Caf with 100 nM Ca2+ medium did not protect 1799-treated cells. Reduced pH and glycine protected 1799-treated cells without ameliorating the increases of Caf. These data demonstrate the toxic potential of increased Caf in the proximal tubule and show that Caf does sharply increase prior to loss of viability in an ATP depletion model of injury, but this increase does not necessarily contribute to the outcome. The potent protective actions of decreased pH and glycine allow the cells to sustain increases of Caf to micromolar levels in spite of severe, accompanying cellular ATP depletion without developing lethal cell injury.